Research on the Application of Virtual Reality Technology in the Elderly Sports Industry in the Era of Big Data - Sheng Gao; Liang Tang (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The rapid development of artificial intelligence technology has resulted in the growth of every single technology under it such as machine learning and deep learning technologies. This research focus on the Immersive Technology names as Virtual Reality and Big data and how they both are correlated in the aspects of elderly sports. The trainer of any virtual reality technology in geriatric sports faces significant obstacles in monitoring and doing exercises, training, monitoring the player’s actions, and food monitoring. The coach uses the most up-to-date information technology to keep track of the player within that regard. The coach and also the players are taught how to use mobile applications to communicate with one another in an interactive way. Also, even if the athlete is located in a rural place, the coach might recommend some monitoring tools to be acquired and used for ongoing checking of a player’s activity. In this research, neural network model has been used to analyze the application of Virtual Reality Technology in the elderly sports Industry in the era of big data. The results provided an accuracy of 99.89% in evaluating the performance.